Avaliações ecocardiográfica e radiográfica do coração em cães da raça Yorkshire Terrier clinicamente normais - Michelle Garcia de Castro (2010)
The aim of this study was to establish the normal echocardiographic and VHS values for Yorkshire Terrier dogs. Thirty clinically normal dogs were studied. The animals were subjected to right lateral, ventrodorsal and dorsoventral thoracic radiographs. The VHS was 9,9 0,6 vertebrae on lateral, 10,1 0,6 on VD and 10,0 0,6 on DV radiographs. There was no significant difference among these values. Five animals (16,67%) presented VHS values exceeding 10,5, value suggested by Buchanan e Bücheler (1995) as upper limit for most breeds in lateral views. Thus, for Yorkshire Terrier dogs, the upper limit should be equal to 11 vertebrae. The VHS values had significant correlation with body weight on lateral and VD radiographs. The echocardiographic parameters were determined, and the left atrial diameter, the aortic diameter, the left ventricular internal dimension at end-diastole and end-systole, end-diastolic and end-systolic interventricular septal thickness, and end-diastolic and end-systolic left ventricular posterior wall thickness had significant correlation with body weight. The other M-mode variables showed no linear correlations with body weight, sex or age. On Doppler echocardiography, the mitral, tricuspid, pulmonic and aortic valves flows were studied. It was found no significant correlation between these variables and body weight, sex or age